Relationship between boundary layer heights and growth rates with ground‐level ozone in Houston, Texas. Issue 10 (27th May 2014) - Haman, C. L.; Couzo, E.; Flynn, J. H.; Vizuete, W.; Heffron, B.; Lefer, B. L.
Abstract Measurements and predictions of ambient ozone (O3), planetary boundary layer (PBL) height, the surface energy budget, wind speed, and other meteorological parameters were made near downtown Houston, Texas, and were used to investigate meteorological controls on elevated levels of ground‐level O3. Days during the study period (1 April 2009 to 31 December 2010 for measurements and 15 April 2009 to 17 October 2009 for modeled) were classified into low (LO3) and high ozone (HO3) days. The majority of observed high HO3 days occurred in a postfrontal environment. Observations showed there is not a significant difference in daily maximum PBL heights on HO3 and LO3 days. Modeling results showed large differences between maximum PBL heights on HO3 and LO3 days. Nighttime and early morning observed and modeled PBL heights are consistently lower on HO3 days than on LO3 days. The observed spring LO3 days had the most rapid early morning PBL growth (~350 m h−1) while the fall HO3 group had the slowest (~200 m h−1). The predicted maximum average hourly morning PBL growth rates were greater on HO3 (624 m h−1) days than LO3 days (361 m h−1). Observed turbulent mixing parameters were up to 2–3 times weaker on HO3 days, which indicate large‐scale subsidence associated with high‐pressure systems (leading to clear skies and weak winds) substantially suppresses mixing. Lower surface layer ventilation coefficients were present in the morning on HO3 days in the spring and fall, which promotes the accumulation of O3 precursors near the surface.